2021
DOI: 10.1039/d1cp02915k
|View full text |Cite
|
Sign up to set email alerts
|

Endohedral group-14-element clusters TM@E9(TM = Co, Ni, Cu; E = Ge, Sn, Pb) and their low-dimensional nanostructures: a first-principles study

Abstract: The endohedral group-14-based clusters with the encapsulation of transition metal, which are termed as [TM@Em]n- (TM = transition metal, E = group-14 elements), have lots of potential applications and have...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…The phenomena that Coulomb interaction ΔE elstat contributes higher than the orbital interaction ΔE orb has been observed in endohedral TM@E 9 (TM = Co, Ni, Cu; E = Ge, Sn, Pb) anions. [22] Both ΔE elstat and ΔE orb decrease from X = F to I, while ΔE Pauli keeps almost constant, leading to a reducing ΔE int trend from X = F to I.…”
Section: Resultsmentioning
confidence: 99%
“…The phenomena that Coulomb interaction ΔE elstat contributes higher than the orbital interaction ΔE orb has been observed in endohedral TM@E 9 (TM = Co, Ni, Cu; E = Ge, Sn, Pb) anions. [22] Both ΔE elstat and ΔE orb decrease from X = F to I, while ΔE Pauli keeps almost constant, leading to a reducing ΔE int trend from X = F to I.…”
Section: Resultsmentioning
confidence: 99%
“…First, the HOMO‐LUMO gap which could be used to assess the stability of clusters is ranging from 0.18 to 1.30 eV. The gaps here are obviously smaller than those of the [TM@E 9 ] n − (TM = Co, Ni, Cu; E = Ge, Sn, Pb; n = 5–3) clusters, 41 indicating the relatively lower stability of [TM@E 10 ] n − clusters. In particular, the HOMO‐LUMO gap of [Ni@E 10 ] n − series are all above 1 eV.…”
Section: Resultsmentioning
confidence: 89%
“…40 Previous studies on Group 14 Zintl clusters have shown that the PBE0/ def2-TZVPPD with PCM(H 2 O) could provide reliable results close to the experimental observations. 9,41 The atomic charge distribution and bond orders were computed via natural bond orbital (NBO) 42 at PBE0/def2-TZVPPD. All the above calculations were conducted by employing Gaussian 09 program.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we found that the EDA analysis could describe the bonding nature of EMFs [56] and Zintl clusters [57,58] well. Thus, to study the bonding nature between the encapsulated metal and fullerenes C 28 , we performed the EDA analysis on TM@C 28 .…”
Section: Emfs (Singletmentioning
confidence: 99%